“The Anointing In The Books Of The Torah Brings God's Approval” - Tri Subekti (International Journal of Christian Education and Philosophical Inquiry, 2024)
The Law of Torah states that the nature of man is a creature of the Creator of the universe who is Spirit. When God created man, Adam, He formed him from the dust of the ground. When God breathed His Spirit into the newly formed man, he became alive, physically, mentally and spiritually. Worship of God is a logical consequence of man because of creation. The purpose of the anointing is so that worshipers are adapted to the nature of the Most Holy God. Thus they are pleasing to God. The reason is, man has fallen into sin. Sin separates him from the presence of the Most Holy God. The curse and hardship of life make man aware that he needs God in his life. The problem is, man with his own efforts from his own ideas will not be pleasing and able to approach God. Sin does not allow man to approach the holy God. This study uses a qualitative method in order to describe and to gain an understanding of the values and qualities of the anointing in the Law of Torah.